Tenecteplase–Tissue-Type Plasminogen Activator Evaluation for Minor Ischemic Stroke With Proven Occlusion. Issue 3 (March 2015) - Coutts, Shelagh B.; Dubuc, Véronique; Mandzia, Jennifer; Kenney, Carol; Demchuk, Andrew M.; Smith, Eric E.; Subramaniam, Suresh; Goyal, Mayank; Patil, Shivanand; Menon, Bijoy K.; Barber, Philip A.; Dowlatshahi, Dar; et al.
Abstract : Background and Purpose—: Minor stroke and transient ischemic attack with an intracranial occlusion are associated with neurological deterioration and disability. Tenecteplase (TNK–tissue-type plasminogen activator) compared with alteplase is easier to administer, has a longer half-life, higher fibrin specificity, possibly a lower rate of intracranial hemorrhage, and may be an ideal thrombolytic agent in this population. Methods—: TNK–Tissue-Type Plasminogen Activator Evaluation for Minor Ischemic Stroke With Proven Occlusion (TEMPO-1) was a multicenter, prospective, uncontrolled, TNK–tissue-type plasminogen activator dose-escalation, safety, and feasibility trial. Patients with a National Institutes of Health Stroke Scale ⩽5 within 12 hours of symptom onset, intracranial arterial occlusion on computed tomographic angiography and absence of well-evolved infarction were eligible. Fifty patients were enrolled; 25 patients at a dose of 0.1 mg/kg, and 25 patients at 0.25 mg/kg. Primary outcome was the rate of drug-related serious adverse events. Secondary outcomes included recanalization and 90-day neurological outcome (modified Rankin Scale, 0–1). Results—: Median baseline National Institutes of Health Stroke Scale was 2.5 (interquartile range, 1), and median age was 71 (interquartile range, 22) years. There were no drug-related serious adverse events in tier 1. In tier 2, there was 1 symptomatic intracranial hemorrhage (4%; 95% confidence interval, 0.01–20.0). Stroke progression occurred in 6% of cases. Overall, 66% had excellent functional outcome (modified Rankin Scale, 0–1) at 90 days. Recanalization rates were high; 0.1 mg/kg (39% complete and 17% partial), 0.25 mg/kg (52% complete and 9% partial). Complete recanalization was significantly related to excellent functional outcome (modified Rankin Scale, 0–1) at 90 days (relative risk, 1.65; 95% confidence interval, 1.09–2.5; P =0.026). Conclusions—: Administration of TNK–tissue-type plasminogen activator in minor stroke with intracranial occlusion is both feasible and safe. A larger randomized controlled trial is needed to prove that this treatment is efficacious. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01654445. Abstract : Supplemental Digital Content is available in the text.